PERUBAHAN PENGGUNAAN MODALITAS INTENSIONAL DALAM BAHASA MELAYU DAN BAHASA INDONESIA - Kurniasih, Ulfa (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Modality is the means of the speaker for his involvement in the truth of his speech propositions. In the semantic level, modalities can appear in all languages with their respective expressions. Modalities according to Alwi (1992) consist of intentional modalities, epistemic modalities, deontic modalities, and dynamic modalities. This study aims to look at changes in use in the aspects of intentional modalities in Malay and Indonesian. The data taken is in the form of Malay texts Hikayat Hang Tuah (1700), Hikayat Indera Nata (1800), and Ronggeng Dukuh Paruk (1982)..